Prevalence of chronic pain in Pakistan – a national survey - Amjad, Muhammad Ammar; Athar Mukhtar Siddiqui; Khalid Bashir; Ateeq Ur Rehman Ghafoor; Romana Shaida Durrani (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess the prevalence of chronic pain, its physical and psychosocial impact on daily life, and the various therapies adopted to alleviate pain. Method: The cross-sectional population-based telephonic survey was conducted from May to July 2021 at Shaukat Khanum Memorial Cancer Hospital, Lahore, Pakistan, and comprised patients of either gender aged at least 18 years suffering from chronic pain who visited the institutional laboratory collection centres. In the first phase, people who were suffering from chronic pain were screened, while in the second phase, data was collected using a detailed questionnaire exploring pain history, treatment and its effects. The data was compiled and analysed using Antlere’s AI based software. Results: Of the 4,801 patients contacted, 757(15.75%) were suffering from chronic pain (15.75%). (201, 20%) subjects reported that there pain score was 5/10 on the numerical rating scale. Back pain was the major complaint (183, 18%) among the subjects. Of the total, 335(44.25%) were having active treatment, and 226 (67%) of them said the medication was effective. Overall, 706 (93%) patients had never visited a pain management specialist. Furthermore, 252 (33%) participants were diagnosed with depression, and 106 (14%) patients said that they were suicidal at some point in life. Conclusion: There was found to be a serious lack of awareness regarding pain management. Key Words: Chronic, Pain, Pakistan, Survey, Prevalence, Back Pain.